2020
DOI: 10.1186/s12898-020-00327-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a spatially heterogeneous nutrient distribution on the growth of clonal wetland plants

Abstract: Background Clonal plants are important in maintaining wetland ecosystems. The main growth types of clonal plants are the guerrilla and phalanx types. However, little is known about the effects of these different clonal growth types on plant plasticity in response to heterogeneous resource distribution. We compared the growth performance of clonal wetland plants exhibiting the two growth forms (guerrilla growth form: Scirpus yagara, Typha orientalis, Phragmites australis and Sparganium stoloniferum; phalanx gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…Our results were supported by previous studies that indicated that flooding along with nitrogen promotes the growth of invasive plant species [36]. Therefore, WT and WC can survive in nitrogen enrichment and flooding conditions due to elongation of plant height that was plant approach to survive with these conditions [37,38]. Plant height increment was plant response to flooding and high nitrogen, to get connect with air and sunlight to do photosynthesis process for its growth development [39].…”
Section: Functional Traits Under Treatmentssupporting
confidence: 88%
“…Our results were supported by previous studies that indicated that flooding along with nitrogen promotes the growth of invasive plant species [36]. Therefore, WT and WC can survive in nitrogen enrichment and flooding conditions due to elongation of plant height that was plant approach to survive with these conditions [37,38]. Plant height increment was plant response to flooding and high nitrogen, to get connect with air and sunlight to do photosynthesis process for its growth development [39].…”
Section: Functional Traits Under Treatmentssupporting
confidence: 88%
“…Clonal growth provides a competitive advantage in community development, species diversity, and community composition [28,29]. Extensive clonal growth may be a major reason for the rapid diffusion of the D. trifoliata population in mangroves, and similar results were verified for other liana species [28,30,31].…”
Section: Introductionmentioning
confidence: 56%
“…As a result, clonal species have an advantage with respect to biomass accumulation in more spatially heterogeneous environments. However, particular types of clonal structures are associated with adaptations to habitats with different degrees of heterogeneity: in relatively homogeneous and stable habitats, clonal plants usually exhibit aggregated structure (phalanx morphology) with short spacer distances, but clonal plants with long spacers (guerrilla morphology) usually prevail in highly heterogeneous and dynamic or disturbed habitats [ 117 , 120 , 121 ].…”
Section: Effect Of Environmental Factors On Water Contentmentioning
confidence: 99%